Initial Evidence for Symptoms of Postpartum Parent-Infant Relationship Obsessive Compulsive Disorder (PI-ROCD) and Associated Risk for Perturbed Maternal Behavior and Infant Social Disengagement From Mother - Ratzoni, Nathalie; Doron, Guy; Frenkel, Tahl I. (Frontiers in Psychiatry, 2021)
Infant socioemotional development and underlying brain maturation occur primarily within the context of early caregiver-infant relationships. Perinatal research demonstrates detrimental impact of postpartum pathology, including postnatal onset of maternal OCD - on the mother-infant relationship. The present study is the first to examine postnatal onset of a particular dimension of OCD focusing on close interpersonal relationships (relationship-OCD, i.e. ROCD). Specifically, we assessed whether symptoms of Parent-Child ROCD (PC-ROCD), may onset postnatally culminating in Parent-Infant ROCD (PI-ROCD). We adapted the previously validated Parent-Child ROCD measure for use during infancy to assess symptoms of PI-ROCD. The adapted measure, Parent-Infant Relationship Obsessive Compulsive Symptoms Inventory (PI-PROCSI), was administered to one hundred and forty-three mothers from the general population at 4-months postpartum. We investigated concurrent associations between postnatal onset of PI-ROCD, maternal depression and bonding, as well as longitudinal predictive associations with observed maternal and infant behaviors in dyadic interactions at 10 months. PI-PROCSI scores explained unique variance in concurrent maternal depression over and above concurrent anxiety. PI-PROCSI scores also associated with concurrent impairments of maternal bonding. Moreover, unique associations emerged between maternal PI-ROCD scores and perturbations in both maternal and infant observable behaviors at 10-months. Specifically, observable perturbations in maternal behaviors mediated associations between symptoms of PI-ROCD at 4-months and observable infant avoidance of social engagement behaviors at 10-months. Findings suggest that parent-child ROCD symptoms may onset during the postnatal period, and that such symptoms may play a significant role in shaping quality of reciprocal caregiver-infant interactions. Theoretical and clinical implications are discussed.